Thailand : an analysis of structural and non-structural adjustmen ts - Drud, Arne; Grais, Wafik, 1949-; Vujovic, Dusan (Washington, D.C. : The World Bank, 1982)
"June 1982"
Keywords: Thailand -- Economic conditions -- Mathematical models